Structural and miqrostructural changes in Zirconia in dilute chlorine atmosphere - Pasquevich, Daniel M.; Lovey, Francisco Carlos (Comisión Nacional de Energía Atómica; Argentina, 1988)
Fil: Pasquevich, Daniel M. Comisión Nacional de Energía Atómica; Argentina